2022
DOI: 10.3390/jcm11206224
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Treatments of Post-Concussion Symptoms

Abstract: Approximately 10–20% of patients who have sustained a mild Traumatic Brain Injury (mTBI) show persistent post-concussion symptoms (PCS). This review aims to summarize the level of evidence concerning interventions for PCS. Following the PRISMA guidelines, we conducted a systematic review regarding interventions for PCS post-mTBI until August 2021 using the Medline, Cochrane, and Embase databases. Inclusion criteria were the following: (1) intervention focusing on PCS after mTBI, (2) presence of a control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Managing anxiety may reduce ongoing symptoms [ 58 ]. Moreover, managing socioeconomic and family-related stressors plays a crucial role in managing the effects of persistent PCS [ 49 , 59 ]. Furthermore, pharmacological treatment [ 60 ], such as acute or preventive medications for primary headache disorders, is useful [ 19 , 25 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Managing anxiety may reduce ongoing symptoms [ 58 ]. Moreover, managing socioeconomic and family-related stressors plays a crucial role in managing the effects of persistent PCS [ 49 , 59 ]. Furthermore, pharmacological treatment [ 60 ], such as acute or preventive medications for primary headache disorders, is useful [ 19 , 25 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-based recommendations for effective non-pharmacological treatment for people with PPCS are sparse (16). However, early written or oral information, reassurance, and advice are recommended (16,32). Hence, providing EUC as standard treatment to all participants is considered most ethically sound for current participants, although potentially limiting the possibility to demonstrate a potential treatment effect of GAIN Lite for future people with mild to moderate PPCS.…”
Section: Explanation For the Choice Of Comparators {6b}mentioning
confidence: 99%
“…Results from studies evaluating the various treatment modalities are mixed, which limits the conclusions that can be drawn. In general, graded physical activity, psychoeducation, and cognitive training had potential as effective therapies for concussion by some reviewers, 25,26 whereas others concluded that rest is underused and more evidence is needed to determine the effectiveness of graded return to physical activity 27 . Strict rest and intense physical activity were found to be either ineffective or detrimental with respect to symptomatic improvement or neurocognitive assessment in children in randomized controlled trials (RCTs) despite demonstrating a beneficial effect in small retrospective studies 26–28 .…”
Section: Introductionmentioning
confidence: 99%